AVALIAÇÃO ULTRASSONOGRÁFICA DO DI METRO DA BAINHA DO NERVO ÓPTICO EM PROSTATECTOMIAS: REVISÃO DE LITERATURA - Cardoso, Therick; Andrino da Silva, Wallace; Klênio Confessor de Sousa, Raphael; Marinho de Araújo, Elkanah; França Bezerra, Isabelle; Pereira Barreto, George (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2022)
Introduction: Neuroimaging assessment and neuromonitoring are important in the treatment of patients at risk of severe acute brain injury. However, the neurological examination may be unreliable, either due to sedation or the patient's baseline status. Therefore, a non-invasive and easily accessible tool stands out, the measurement of the Optic Nerve Sheath Diameter (ONSD), which is related to Intracranial Pressure (ICP). Objective: To review the literature, summarizing the evidence related to the measurement of ONSD in prostatectomies for the analysis of intraoperative ICP. Method: The paper's search was performed in Pubmed/Medline, Lilacs and Google Scholar databases, using the descriptors: intracranial pressure AND ultrasound AND optic nerve AND prostatectomy. Results: 30 articles were selected, 20 of which were excluded because they did not adequately discuss the proposed theme. Conclusion: ONSD is a very useful method for determining ICP increase, especially during Robot-Assisted Laparoscopic Radical Prostatectomy (RALRP), which may be associated with inadequate emergence of anesthesia. Dexmedetomidine, administered during the course of surgery, attenuates the increase in ICP during pneumoperitoneum in the Trendelenburg position. Finally, propofol reduces ICP changes in patients undergoing robotic surgery in comparison to sevoflurane.